Treatment outcomes and objectification methods of the thoracoscopic sympathectomy in patients with focal hyperhidrosis and blushing syndrome - Eroshkin, Oleksii A.; Sokolov, Vitaliy V.; Omelchenko, Anastasiia V.; Luzhenetska, Iryna R.; Romanukha, Dmytro M. (Ukrainian Neurosurgical Journal, 2021)
Uniportal video-assisted thoracoscopic sympathectomy (VATS) is an effective minimally invasive surgical method of choice for the treatment of primary focal hyperhidrosis and blushing syndrome due to uncontrolled operation of the sympathetic nervous system. The aim of this study was to provide an objective assessment of the improvement in the quality of life of patients with primary focal hyperhidrosis and blushing syndrome after bilateral monoport video-assisted thoracoscopic sympathectomy. Materials and methods. The results of surgical treatment were performed for 62 patients aged 17 to 42 years, 26 men and 36 women with a diagnosis of primary focal hyperhidrosis of the extremities and blushing syndrome. All patients underwent bilateral uniport video-assisted thoracoscopic sympathectomy. Patients are divided into 3 groups depending on the level of coagulation of the sympathetic trunk: the first group of the study (n = 9) includes patients after bilateral uniport sympathectomy at the level of R3 (isolated palmar hyperhidrosis), the second (n = 31) - at the level of R3-R4 (palmar and axillary hyperhidrosis), the third group (n = 22) - at the level of R2 (blushing syndrome). Results. In this study, coagulation and separation of the sympathetic trunk through a single port using a silicone port was performed. An excellent clinical result was achieved due to the minimally invasive operation - all 62 patients (100%) were satisfied with the achievement of a rapid stable effect. According to the results of the Dermatology Life Quality Index DLQI (1 month after surgery), the best quality of life measures were observed in patients who underwent separation of the sympathetic trunk at the R3 level – improvement from 20.3 ± 5.9 points to 0.8 ± 0.8 points. After the operation at the R3-R4 level scores the quality of life decreased from 22.77 ± 5.4 points to 2.3 ± 1.3 points, and at the level of R2 - from 16.5 points (QI 14 points - QIII 20 points) to 2 points (QI 1 point - QIII 3 points) p <0.001). There was a difference in quality of life measures in our three groups of patients according to the severity of the disease before surgery. The lowest quality of life was determined in patients with the 4th degree of severity (33 people) and was 26.0 points (QI 23.0 points - QIII 27.3 points) compared with patients with 2d and 3d degrees of severity, 10.0 points (QI 7.7 points - QIII 10.0 points) and 17.0 points (QI 14.0 points - QIII 19.5 points) respectively (p <0.001). After a single-port VATS in three groups there was an increase in quality of life measure, regardless of the severity of the disease before surgery. Conclusions. The most highly specific tests that allow to determine an objective assessment of the severity of the disease and a real assessment of the effectiveness of surgical treatment for hyperhidrosis was TEWL-metry, for blushing syndrome – capillaroscopy. VATS is an effective method of treating patients with hyperhidrosis and blushing syndrome, which significantly improves the quality of life according to the results of the Dermatological Index of Life Quality DLQI (p <0.001) questionnaire.